Forced labor in the "People's Democracies". Ed. R.K. Carlton. Research and analysis by A.G. Caranfil. J. Hajdukiewicz, J. Ledecky [a.o.] (Praeger, 1955)
Published for the Mid-European Studies Center of the Free Europe Committee.